Upgrading of bio-oil into advanced biofuels and chemicals, Part III: Changes in aromatic structure and coke forming propensity during the catalytic hydrotreatment of a fast pyrolysis bio-oil with Pd/C catalyst - Li, X.; Gunawan, Richard; Wang, Y.; Chaiwat, W.; Hu, Xun; Gholizadeh, M.; Mourant, D.; Bromly, John; Li, Chun-Zhu (Elsevier Ltd, 2013)
This study has investigated the hydrotreatment of bio-oil (derived from the fast pyrolysis of mallee woody biomass) in a batch reactor under 10 MPa pressure with Pd/C catalyst at temperatures between 150 °C and 300 °C. Our results indicate that the chemical fractions, coking tendency as well as the aromatic structures are highly influenced by the hydrotreating conditions such as temperature and time. The repolymerisation surpasses the hydrogenation of bio-oil at the low hydrotreating temperatures (e.g. 150–200 °C) and short hydrotreating durations (e.g. <3 h). On the contrary, high hydrotreating temperatures (e.g. 250–300 °C) and long reaction durations (e.g. 6–12 h) can effectively convert the heavier fractions into lighter fractions, and thus further reduce the coking tendency of the hydrotreated products. However, these harsh operational conditions cannot decrease the number of large aromatic ring systems. Most importantly, it is found that the combination of esterification and hydrotreatment can produce more stable bio-oil with lower coking tendency and less large aromatic ring systems than the direct hydrotreatment of bio-oil.